2007
DOI: 10.1002/app.24944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ATH content on electrical and aging properties of EVA and silicone rubber blends for high voltage insulator compound

Abstract: The effect of trihydrated alumina (Al 2 O 3 , 3H 2 O) (ATH) filler in ethylene-vinyl acetate copolymer (EVA) and silicone rubber blends was investigated by performing a series of laboratory experiments to simulate different natural aging conditions. Samples with varying ATH content in a 50-50 blend of EVA and polydimethylsiloxane (PDMS) (silicone rubber, MQ) were tested to investigate the tracking resistance, resistance to UV radiation, corona, heat, and water immersion. Changes in surface resistivity, volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
2
30
1
Order By: Relevance
“…In other words, the ATH concentration was the most reduced for aged HTV elastomer. This ATH defect could be interpreted as being at the origin of the low value of the corona inception voltage as already proposed by Pradeep [33]. But, at the same time, one of the liners taken from new production presented an ATH concentration higher than that of the used liner whereas the respective insulator inception corona voltage was slightly lower (10 kV against 12 kV).…”
Section: Ftir Analysessupporting
confidence: 60%
“…In other words, the ATH concentration was the most reduced for aged HTV elastomer. This ATH defect could be interpreted as being at the origin of the low value of the corona inception voltage as already proposed by Pradeep [33]. But, at the same time, one of the liners taken from new production presented an ATH concentration higher than that of the used liner whereas the respective insulator inception corona voltage was slightly lower (10 kV against 12 kV).…”
Section: Ftir Analysessupporting
confidence: 60%
“…Polydimethylsiloxanes (PDMS) are widely used for polymer blends because of their gas barrier and electrical properties, their low glass-transition temperature, their low surface energy and high thermal, UV and oxidative stabilities [1]. However, due to their low surface energy and relatively low viscosity compared to most thermoplastics, the dispersion of PDMS is generally difficult and results in phase segregation of PDMS in most polymer blend systems.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] However, their low effectiveness makes it necessary to incorporate them at a very high content to gain a satisfying flame retardancy, which leads to a poor dispersion and damage of the material's mechanical properties. [8] What's more, the particle size and types of flame retardants are also of great importance in flame-retarding behavior. For instance, Li et al [9] has reported that the flame-retardant effect of ATH was better than that of MDH for similar shapes and particle sizes in ethylene-vinyl acetate.…”
Section: Introductionmentioning
confidence: 99%